Biocalcium powder from precooked skipjack tuna bone: Production and its characteristics. Issue 6 (7th August 2017) - Benjakul, Soottawat; Mad‐Ali, Sulaiman; Senphan, Theeraphol; Sookchoo, Pornsatit
Abstract: Biocalcium (BC) powder from the bones of precooked skipjack tuna was produced and characterized, compared to calcined bone (CB) powder. Higher calcium (40.35%) and phosphorous (15.28%) contents were found in the CB powder, compared to BC powder (26.91 and 12.63%, respectively). Nevertheless, similar Ca/P ratio was observed (1.62–1.65). Mean particle sizes of both powders were 17.07–20.29 µm. BC powder had higher b * (yellowness) with slightly lower L * (lightness) values than the CB counterpart ( p  < .05). Both samples showed a characteristic peak of hydroxyapatite in X‐ray diffraction patterns, in which the crystallinities of the BC and CB powders were 45.19 and 74.69%, respectively. Amides I, II, and III peaks in Fourier transform infrared spectrum, hydroxyproline, and protein were detected only in the BC powder. BC powder had a low abundance of volatile compounds, including aldehydes, alcohols, and ketones. A negligible amount of volatiles was found in the CB powder. Practical applications: Calcium supplementation has been increasingly used to alleviate the lack of calcium in the human body, particularly inadequate levels of calcium and poor absorption. Calcium associated with peptides or biocalcium (BC) has a higher advantage in terms of absorption than calcium alone. Precooked skipjack tuna is considered a promising source for BC production due to its abundance. BC with improved color and odor along with increased solubility in gastrointestinal tract can be used as an alternative calcium supplement to tackle the inadequate intake of dietary calcium.